Distribution of the National Early Warning Score (NEWS) in care home residents. (9th December 2019) - Barker, Robert Oliver; Stocker, Rachel; Russell, Siân; Roberts, Anthony; Kingston, Andrew; Adamson, Joy; Hanratty, Barbara
Abstract: Background: the National Early Warning Score (NEWS) is a tool based on vital signs that aims to standardise detection of, and response to, clinical deterioration in adults. NEWS has been adopted in hospitals but not adapted for other settings. This study aimed to explore the feasibility of measuring the NEWS in care homes and describe the distribution of NEWS readings amongst care home residents. Methods: descriptive analysis of all NEWS readings recorded in a 30-month period (2016–19) across 46 care homes in one Clinical Commissioning Group in England. Comparisons were made between measurements taken as a routine reading and those prompted by concern about acute illness. Results: a total of 19, 604 NEWS were recorded from 2, 424 older adults (≥65 years; mean age 85). Median NEWS was 2. Two thirds (66%) of residents had a low NEWS (≤2), and 28% had a score of 0. Of the total NEWS readings, 6, 277 (32%) were known to be routine readings and 2, 256 (12%) were measured because of staff concerns. Median NEWS was 1 for routine and 2 for concern recordings. Overall, only 12% of NEWS were high (≥5), but a higher proportion were elevated when there were concerns about acute illness (18%), compared with routine recordings (7%). Conclusions: use of NEWS in care homes appears to be feasible. The majority of NEWS were not elevated, and the distribution of scores is consistent with other out-of-hospital settings. Further work is required to know if NEWS is triggering the most appropriate response and improving care home resident outcomes.